Global prevalence of help‐seeking for problem gambling: A systematic review and meta‐analysis. (13th July 2022) - Bijker, Rimke; Booth, Natalia; Merkouris, Stephanie S.; Dowling, Nicki A.; Rodda, Simone N.
Abstract: Background and Aims: Multiple studies have examined barriers and facilitators to help‐seeking, but the prevalence of help‐seeking for problem gambling (PG) is not well established. We aimed to estimate the international prevalence of help‐seeking for PG among the general population and among subgroups of people at risk for PG (i.e. low‐risk, moderate‐risk and PG). Methods: Systematic search of grey literature (through gambling repositories, gambling research institutes and Google) and peer‐reviewed literature (through ProQuest, PsycINFO, PubMed and Scopus) for gambling prevalence studies that reported on help‐seeking for PG. This review adhered to the Preferred Reporting Items for Systematic Review and Meta‐Analyses. Studies used representative sampling methods to determine the prevalence of gambling participation and data collection 2010 onward. Twenty‐four studies met the inclusion criteria. The main outcome was population prevalence of help‐seeking for PG. Help‐seeking was defined as any intentional action to change gambling behaviours, including professional services (inclusive of in‐person or distance help), non‐professional help (e.g. from family and friends) and self‐help. Subgroup analyses were conducted to explain variability in help‐seeking prevalence estimates. Results: Measurement of help‐seeking was inconsistent across included studies and, overall, there was high risk of bias. We estimated a general population help‐seeking prevalence for PG of 0.23% (95% CI, 0.16–0.33). Prevalence estimates were significantly higher in studies assessing lifetime (0.50%; 95% CI, 0.35–0.71) compared with current help‐seeking (0.14%; 95% CI, 0.10–0.20, P < 0.001), but there was no evidence of difference in prevalence estimates by gambling participation, region, type of help‐seeking, or year of data collection. Compared with people with low‐risk gambling (0.27%; 95% CI, 0.07%–1.04%), prevalence estimates were significantly higher in those with moderate‐risk (3.73%; 95% CI, 2.07%–6.63%) and problem gambling (20.63%; 95% CI, 12.89%–31.35%, P < 0.001). Conclusions: One in 25 moderate‐risk gamblers and 1 in 5 people with problem gambling have sought help for problems related to their gambling.